Screw fixation in the treatment of displaced intra-articular calcaneus fractures: a systematic review protocol - Leah Wilmsen; Anne Neubert; Joachim Windolf; Andrea Icks; Bernd Richter; Simon Thelen (Systematic Reviews, 2022)
Abstract Background The Calcaneus is the largest bone of the foot and the most frequent tarsal bone to be fractured. Overall, it causes round about 10 cases per 100,000 residents per year mainly in men. Especially displaced intra-articular calcaneus fractures often have early and late complications and its associated disability. There are various strategies for the treatment of displaced intra-articular calcaneus fractures, but the gold standard is still subject of a long-standing controversy. Minimally invasive procedures became more common in an attempt to reduce the high rate of complications associated with open reduction and internal fixation. With the increase in minimally invasive techniques, screw fixation also gained in significance. The current literature does not sufficiently elucidate whether the screw fixation is superior to other treatment options especially in relation to adverse events, health-related quality of life and postoperative pain. This study aims to investigate benefits and harms of treating displaced intra-articular calcaneus fractures (types II, III and IV according to Sanders) with screw fixation in adults. Methods A systematic review will be conducted based on the principles described in the Cochrane Handbook. We will include adults with displaced intra-articular calcaneus fractures of Sanders type II, III and IV. The surgical method of screw fixation shall be compared to other surgical interventions to stabilise calcaneus fractures. Primary outcomes are serious adverse events, health-related quality of life and postoperative pain level. MEDLINE, CENTRAL, CINAHL, Web of Science and bibnet.org, ClinicalTrial.gov and the World Health Organization International Clinical Trials Registry Platform (ICTR) will be searched. Screening and data extraction will be performed by two authors independently. A third author will arbitrate disputes. Risk of Bias will be assessed with the Cochrane tool. Meta-analysis will be performed if participants, interventions, comparisons and outcomes are sufficiently similar to ensure a result that is clinically meaningful. Discussion Due to the increasing use of minimally invasive techniques and the increasing use of screw fixation instead of open reduction and plate fixation, it is important to analyse the benefits and harms of screw fixation for calcaneus fractures. Screw fixation could, in the future, help to operate in a less invasive and tissue preserving manner while still achieving an adequate functional result for the patient Systematic review registration CRD42021244695